Portable gluten sensors: qualitative assessments by adults and adolescents with coeliac disease. Issue 6 (25th September 2020) - Wolf, R. L.; Vipperman‐Cohen, A.; Green, P. H. R.; Lee, A. R.; Reilly, N. R.; Zybert, P.; Lebwohl, B.
Abstract: Background: Portable gluten sensors are now commercially available to the public, although there is genuine uncertainty within the medical community over whether they should be used for coeliac disease management. The present study described qualitatively the experience of using a portable gluten sensor for 15 adults and 15 adolescents with coeliac disease participating in a 3‐month pilot clinical trial. Methods: Participants were 30 individuals, aged 13–70 years, with biopsy‐confirmed coeliac disease on a gluten‐free diet. All received a portable gluten sensor and were randomised to low, medium, and high numbers of single‐use capsules. Open‐ended questions addressed likes and dislikes using the portable gluten sensor after 3 months. Major themes were identified and described. Results: Participants liked that the portable gluten sensor provided extra assurance to check foods presented as gluten‐free, the convenient size and portability, the added sense of control, and overall peace‐of‐mind. Participants disliked having attention drawn to them when using the sensor and feeling as if they were deterring others from eating. Participants also disliked the physical difficulty associated with using the capsules, questionable accuracy and the inability to test fermented foods. Adults were more enthusiastic about the sensor than adolescents. Conclusions: Positive and negative experiences may be expected when using commercially available portable gluten sensors to help manage coeliac disease. As future versions of this and other gluten sensors become available, it will be important to investigate the relationship between users' experience with the sensors and long‐term outcomes such as mucosal healing and quality of life. Abstract : Portable gluten sensors are now commercially available to the public, although there is genuine uncertainty within the medical community over whether they should be used for coeliac disease management. Although data are emerging regarding the performance of portable gluten sensors, little is known about patient responses to real‐time access to the data provided. The present study described qualitatively the experience of using a portable gluten sensor by adults and adolescents with coeliac disease participating in a 3‐month pilot clinical trial.